På munkenes bord: Cisterciensernes mad og madkultur i middelalderens Danmark - Mollerup, Lene (Kuml, 2021)
On the monks’ table The food and culinary heritage of the Cistercians in Medieval Denmark An investigation of the food and culinary heritage of the Cistercians in Medieval Denmark, involving a range of multidisciplinary sources, has revealed new connections and relations. These sources work together and support each other in areas where others are silent. This has made it possible to follow the food culture of a specific population group through almost 400 years. The monks in Cistercian abbeys ate two daily meals during the summer half of the year, while they only ate one meal a day in winter. At these mealtimes, each monk was served two hot dishes and half a kilo of bread. There was also the opportunity for young and hardworking monks and lay brothers to take a light breakfast of water/beer and bread. To tame their carnal desires, the monks refrained from eating the meat of four-legged animals. Their diet was primarily based around cereal and vegetable products with some fish, eggs and dairy products. Our knowledge of the food on the monks’ table comes from written sources and the archaeological record. We can see that their meals could be served on, and eaten from, locally produced pottery. The monks had their own personal tankards and jugs, and their dinner knives resembled those of the time. It is possible that the fine carving knife found at Øm Abbey, with a handle carved into the figure of a bishop, was used at the abbot’s table. Bread and porridge were made from barley, oats and rye, and buckwheat also found its way into the gruel pot. We know virtually nothing about the vegetables on the monks’ table. The archaeological record is silent on this point, but it seems likely there was a good mixture of commonly cultivated vegetables such as cabbage, onions, leeks and pulses, as revealed by foreign sources. The third course of fresh fruit and salad would consist of apples, pears, plums, bullaces, cherry plums, figs, peaches and a wealth of berries such as raspberries, blackberries, strawberries and blueberries. Elderberries were similarly known and used, as well as hazelnuts and walnuts. Fresh salads could contain young leaves of ground elder, black mustard and endive (leaves of chicory). Part of the monks’ protein-rich diet consisted of dairy products such as milk and cheese as well as eggs in the time outside Lent. Milk was a seasonal and easily perishable product that could be converted into butter and cheese to increase its keeping qualities. Cheese was made from cow’s, goat’s and sheep’s milk. At Lent, the monks were not allowed to eat animal fat, but they knew how to make plant-based “butter” and other “dairy products” with for example walnuts and probably also almonds. Perhaps they also used linseed oil. There is a 14th century cookbook from Sorø Abbey containing recipes for sauces, dressings and egg- and milk-based dishes, as well as dishes with poultry, all of which could be served at the monks’ table. The cookbook could give the monks some ideas for a little variation in their diet without the rules being broken. The monks received gifts of meals called pittances, which are mentioned in written sources from the period 1200-1400. These give us an idea about what was considered as extra provisioning in the abbey and what they were permitted to accept because it took the form of a gift. We hear about well-prepared and well-seasoned milk and fish dishes, for example using stock fish, as well as dishes with aspic and rice, spiced with pepper, and wheat bread, too. Meat from four-legged animals is not mentioned. Fish was eaten in great quantities in the monasteries, especially during Lent. Finds of fish scales and bones from Øm Abbey’s kitchen floor tell us that it was especially freshwater fish species that were consumed here. Animal bones from Øm’s kitchen midden (which is undated) bear witness to the consumption, in some form or other, of cattle, pigs, sheep, goats and horses, as well as wild boar, roe deer and red deer. When and by whom these were eaten is unclear. We can see from the written sources that the sick were permitted to eat meat and that they were served offal and other by-products from the butchering of four-legged animals, while the prohibition on meat for others was strictly maintained. Dated sources, in the form of analyses of preserved plant macro-remains and pollen and deeds of gift with detailed contents, cannot tell us when meat dishes made their entry into the Danish Cistercian abbeys. Other written sources are, however, very consistent in this respect: From 1439 onwards, Cistercians were permitted to eat meat from four-legged animals during specific periods of the year, and from 1475 they were all allowed to eat meat several times a week. These sources suggest that meat dishes apparently did not find favour on the tables of the Cistercians until late in the Middle Ages, but the archaeological record can unfortunately neither confirm nor refute this. Isotope analyses of human bones from Øm Abbey suggest, on the other hand, that the monks consumed increasing amounts of animal protein during the Middle Ages. Sources relating to the Cistercians’ food and culinary heritage indicate that the Danish Cistercians were long-term members of an international order with the same codes of practice, but in the Late Middle Ages they adapted themselves to a changing society. But what was the monks’ attitude to moderation in relation to food? Is there evidence of well-fed bons vivants? The sources suggest that the Cistercians persistently and consistently stood their ground against gluttony, luxury and meat consumption – longer than the other monastic orders. This was probably easier when the food was produced, cooked, served and eaten communally. Food and the settings for the consumption of meals became increasingly profane with time, and it appears that some enjoyment and pleasure eventually found its way to tables of the fat-averse monks, especially in the form of donated food gifts. But well-fed and hedonistic they are probably unlikely ever to have been. The Cistercians, who began as a reform order and created a unique European monastic culture, were forced to see themselves defeated by the times. The order did, however, reform itself again in the 17th century and returned to “the eternal abandonment of meat”, but then it was too late for the Danish Cistercian abbeys. They had all been abolished at the Reformation in 1536.